Measuring the benefit from reducing income inequality in terms of GDP - Simon Voigts (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
Given that well-being is a concave function of income, inequality is inefficient from a utilitarian perspective. This paper proposes a way to express the utilitarian benefit from redistributive reforms in terms of out- put, i.e. as a share of GDP. Three applications are presented: First, in nine European countries under study, a mild increase in government redis- tribution allows for gains in well-being equivalent to 8.9%-20.2% of higher GDP, and 55.8% for the US. Second, in the US, redistributing income in excess of the level at the 99th percentile is as beneficial as a 39.5% GDP-increment. Third, revoking government redistribution in Germany reduces welfare by the same amount as a 25.4% decline in output.
Keywords: D31; D63; 330; Income Distribution; Inequality